2021
DOI: 10.17533/udea.ikala.v26n2a05
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de un programa de lectoescritura en el rendimiento académico de estudiantes de primer año universitario en Chile

Abstract: En la última década, las instituciones de educación superior han desplegado una serie de programas para enseñar a leer y escribir en este nivel educativo; sin embargo, poco se conoce del efecto de estas iniciativas sobre el rendimiento académico de los estudiantes. El objetivo del presente estudio fue determinar el impacto de uno de estos programas en el desempeño académico de estudiantes de primer año de Psicología que asistían a las sedes regionales de Concepción, Santiago, Puerto Montt y Valdivia de la Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…Given the curricular organisation in subjects, it is possible to affirm that each school subject has a correlated professional grouping: a disciplinary community. New conceptual disambiguation is necessary, as the term disciplinary community can represent the concept of discursive community, generally associated with David Russell’s studies on writing through the curriculum (Carlino, 2005; Chois-Lenis et al, 2020; Martinez et al, 2021; Molina-Natera, 2012; Ochoa-Villanueva and Rengifo-Mattos, 2021; Russell, 1990) and the writings of John M. Swales (Costa, 2012; Navarro, 2013; Pacheco and Bernardino, 2017; Padilla, 2018; Riffo, 2021; Swales, 2016; Ulloa, 2020).…”
Section: Epistemic and Disciplinary Communitiesmentioning
confidence: 99%
“…Given the curricular organisation in subjects, it is possible to affirm that each school subject has a correlated professional grouping: a disciplinary community. New conceptual disambiguation is necessary, as the term disciplinary community can represent the concept of discursive community, generally associated with David Russell’s studies on writing through the curriculum (Carlino, 2005; Chois-Lenis et al, 2020; Martinez et al, 2021; Molina-Natera, 2012; Ochoa-Villanueva and Rengifo-Mattos, 2021; Russell, 1990) and the writings of John M. Swales (Costa, 2012; Navarro, 2013; Pacheco and Bernardino, 2017; Padilla, 2018; Riffo, 2021; Swales, 2016; Ulloa, 2020).…”
Section: Epistemic and Disciplinary Communitiesmentioning
confidence: 99%
“…Several studies were identified related to the influence of attitude with learning and specifically with the performance of complex writing tasks as a part of academic literacy. In education, learning theory, and research, there are a number of constructs that relate closely to attitude and attitudinal learning, including learner beliefs, motivation, self-regulation, and self-efficacy (Watson et al, 2018). Self-efficacy is a type of belief that refers to an individual's judgment of his or her ability to perform the actions necessary to achieve specific goals (Bandura, 1977).…”
Section: The Attitude and Emotional Part Of Learningmentioning
confidence: 99%
“…Two scoping reviews were identified, one with the objective of exploring and describing methods and strategies to promote the development of academic literacy ( Klarare et al, 2022 ) and the other with the objective of completing a characterization of complex thinking in academic literacy and higher education ( Suarez-Brito et al, 2022 ). Five articles were found that addressed interventions, two of them focused on writing ( Olivier, 2019 ; Zashikhina, 2021 ), one aimed at academic writing in English ( Roux et al, 2018 ), one about a Center for Reading, Writing and Orality ( Soares Sito et al, 2019 ), and one research focusing on a program that was designed in such a way as to associate learning with the production and analysis of texts specific to the students’ field of study ( Urzúa-Martínez et al, 2021 ), and another article dealt with a cross-cutting program of academic literacy ( Pardo-Espejo and Villanueva-Roa, 2019 ). In contrast, an investigation was also identified, the objective of which focuses on recognizing poor black youth in rural communities as knowledge givers and knowledge takers or “epistemic contributors” ( Soares Sito, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…"Una forma de estudiar el desarrollo y el ejercicio de la reflexión pedagógica es mediante la identificación de los géneros que se escriben en la formación docente" (Jarpa-Azagra, 2019, p. 88). Así, es imprescindible repensar las prácticas de escritura desde todos los espacios académicos que integran el currículo (Navarro & Revel, 2013;Urzúa-Martínez et al, 2021), con el fin de consolidar la cultura de "si lo escribo, lo he pensado ya muchas veces". De este modo, escribir se asocia al pensar disciplinar, a la esencia de los procesos de aprendizaje, y es la base de la ciencia en el paso a paso de "rumiar" un conocimiento.…”
Section: Alfabetización Académica Y Prácticas De Escritura Como íNdic...unclassified